If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 180 + -1x = 2(180 + -1(90 + -1x)) 180 + -1x = 2(180 + (90 * -1 + -1x * -1)) 180 + -1x = 2(180 + (-90 + 1x)) Combine like terms: 180 + -90 = 90 180 + -1x = 2(90 + 1x) 180 + -1x = (90 * 2 + 1x * 2) 180 + -1x = (180 + 2x) Add '-180' to each side of the equation. 180 + -180 + -1x = 180 + -180 + 2x Combine like terms: 180 + -180 = 0 0 + -1x = 180 + -180 + 2x -1x = 180 + -180 + 2x Combine like terms: 180 + -180 = 0 -1x = 0 + 2x -1x = 2x Solving -1x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1x + -2x = 2x + -2x Combine like terms: -1x + -2x = -3x -3x = 2x + -2x Combine like terms: 2x + -2x = 0 -3x = 0 Divide each side by '-3'. x = 0 Simplifying x = 0
| 2(x-3)=-2+2x | | 3z-14=-8 | | 2x(6-x)=89 | | 2(n-3)=-2+-9 | | -1+4x=-77 | | 15f+6-1f=2f-6 | | 7x-1=2x-4 | | 13t-4(2t-5)=15 | | 16y^3-4y^2-2y=0 | | 2n-6*4=5 | | (3x-7)-5=12 | | 22x=35 | | 12x=37 | | 18x-32=28x/2 | | 1w+2w=24 | | -1a=9 | | 7x+4x=8 | | 7x+7-6x=6 | | 7(x-3)-2x= | | y^3-12y^2+32=0 | | -6(m+1)-2c=24 | | 2x^6-x^4-2x^2+4=0 | | 1.14x=1.25 | | x^2+4=x+4 | | 0.25x=0.275 | | -9+16x=5x+13 | | (2x-9)+3x=16 | | 30-(-2)(4-x)= | | X+19+2x=-18-2x-23 | | 4(-0.142+-0.285y)=-13 | | (x-17.5)*9.5=8.085 | | 30-(2)(4-x)= |